Minimálně invazivní krční elastická laminoplastika - principy a operační technika - Suchomel, Petr; Hradil, Jan (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2011)
To present a new technique of minimally invasive decompression of the cervical spinal canal using elastic and plastic deformation of the laminae. MATERIAL AND METHODS: Short midline vertical incision provides an access to the superior aspect of the target spinous processes. Cranial edge of the lamina is located by a midline, muscle-sparing interspinous dissection. The spinous process is cut in mid-sagittal plane using a thin blade of an ultrasonic bone scalpel down to epidural space. The created sagittal cleavage of the spinous process is subjected to tension and elastic distraction by a custom-designed distractor (Aesculap, Germany). Gradual increase of the distraction force leads to a significant plastic deformation. This reduces the distraction force and allows for a wider exposure which, in turn, facilitates dural visualization, resection of the yellow ligament and undercutting of approximately a half of the adjacent intact laminae. After completion of decompression, the plastic arch expansion can be maintained either by interposed bone-graft or appropriately shaped cage secured by a circumferential suture to the spinous process. Soft tissue resection and permanent expansion of the laminae provide sufficient decompression of the cervical spinal cord. In multilevel stenosis, the desired laminae can be expanded using this technique. To achieve the same degree of canal expansion as that by a classic laminoplasty (C3-7), a skip technique can be utilized. This involves combining expansive laminoplasty of C4 and C6 with bilateral undercutting of C5 and partial undercutting of C3 and C7. This can be achieved through two short vertical incisions. Based on data and experience gained from testing on 11 cadavers, we applied this method in 7 patients requiring posterior cervical decompression. RESULTS: The spinous process or laminae fractured during expansion in the initial 4 patients and the procedure required conversion to a minimally invasive laminectomy. Further modification of the distractor and spinous process splitting technique resulted in elimination of this complication in subsequent cases. In all remaining patients, sufficient canal expansion was achieved by soft tissue resection and distraction of laminae, typically reaching 5 - 8 mm. Minimally-invasive muscle-sparing midline approach provided very positive functional results in terms of postoperative pain and range of motion allowing for immediate mobilization without external bracing. CONCLUSION: Minimally invasive, muscle sparing, expansive laminoplasty provides adequate spinal canal expansion. Use of this technique and its muscle-sparing nature potentially result in improvement of early functional outcomes when compared to standard laminoplasty techniques requiring lateral lamina-facet border exposure. However, the theoretical superiority of this technique will need to be clinically scrutinized in a well designed surgical outcome study.
Keywords: mrtvola; Humans; výsledek terapie; klinické zkoušky jako téma; laminektomie; Treatment Outcome; Cadaver; Cervical Vertebrae; krční obratle; Minimally Invasive Surgical Procedures; miniinvazivní chirurgické výkony; Clinical Trials as Topic; Laminectomy; lidé